Age- and sex-related reference ranges for eight plasma constituents derived from randomly selected adults in a Scottish new town. Issue 4 (April 1980) - Gardner, M D; Scott, R
Abstract : The results of analysis of blood specimens from randomly selected adults aged 19-88 years in the new town of Cumbernauld were used to establish age- and sex-related reference ranges by the centile method (central 95%) for plasma calcium, phosphate, total protein, albumin, globulins, urea, creatinine, and urate. The possible existence of a subpopulation with a higher reference range for urea is mooted.